The Impact of Sacubitril / Valsartan Versus ACE/ARB Therapy on Functional Capacity in Heart Failure with Reduced Ejection Fraction - Yassen, Mohammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.